1984
DOI: 10.1002/cne.902240103
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal differentiation of rat optic nerve fibers: Electron microscopic observations on the development of nodes of Ranvier and axoglial relations

Abstract: The postnatal differentiation of rat optic nerve fibres was examined by transmission electron microscopy. The results show that many early developing axons contain clusters of vesiculotubular profiles prior to myelination. At places vesicular elements appear to fuse with the axolemma, and, in addition, some axons exhibit deep axolemmal invaginations and axoplasmic lamellated bodies. It is suggested that these features might reflect axolemmal remodelling, possibly involving axoglial signalling and/or functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(97 citation statements)
references
References 43 publications
4
91
1
Order By: Relevance
“…The oligodendroglial population of P7 periventricular white matter is less mature than that of the P10 optic nerve, which initiates myelination at BP6 (Hildebrand and Waxman, 1984). Indeed, the cells studied using immuno-EM by Wilke et al (2004) were identified as oligodendrocytes partly on the basis of having compact myelin profiles within their processes, a phenomenon not seen in the P7 cortical oligodendrocytes studied here.…”
Section: Discussionmentioning
confidence: 58%
“…The oligodendroglial population of P7 periventricular white matter is less mature than that of the P10 optic nerve, which initiates myelination at BP6 (Hildebrand and Waxman, 1984). Indeed, the cells studied using immuno-EM by Wilke et al (2004) were identified as oligodendrocytes partly on the basis of having compact myelin profiles within their processes, a phenomenon not seen in the P7 cortical oligodendrocytes studied here.…”
Section: Discussionmentioning
confidence: 58%
“…Nodes and perinodal processes appear together during development, which has raised the question whether their interaction are a factor determining the spacing of nodes (see Hildebrand and Waxman, 1984; reviewed by Black and Waxman, 1988). In this case, however, we found that partition spacing is only a fraction (18%) of the estimated average internode length in mature fish optic nerve fibers.…”
Section: Reinforcing the Optic Nervementioning
confidence: 67%
“…The neural signals of spikes were amplified and filtered with a Cerebus 32-channel system (BlackRock Microsystems). Single units were sorted based on Klustakwik clustering analysis of waveforms (Harris et al, 2001) using a custom-written software for supervision.…”
Section: Methodsmentioning
confidence: 99%